Adaptive Setting Policy for Microcomputer Based Protection Systems - Jenwang He; Vanjing Xiu; A. G. Shpuntova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyses a problem pertaining to improvement of selectivity of microcomputer based protection systems for power transmission lines. It is shown that transient resistance influences on selectivity in the place of fault. An adaptive setting policy and a practical method concerning calculation of a phase angle and adapted inductive reactance are given in the paper.